An Exploratory Study of Augmented Reality for Teaching the Human Skeletal System at SMA Negeri 1 Suwawa - Akbar, Muh. Nur; Mardin, Herinda; Mangge, Aditya Z.; Daud, Pransiska Sunarti (Bioilmi: Jurnal Pendidikan, 2024)
The study addresses the challenges students face in understanding the human skeletal system and the need for innovative learning media. The research aimed to analyze the needs of students and teachers while evaluating the potential of Augmented Reality (AR) cards as a teaching tool. Conducted at SMA Negeri 1 Suwawa, Gorontalo Regency, the study employed a descriptive qualitative approach with data collection through observations, interviews, and student needs surveys. Findings revealed a strong interest among teachers in adopting AR-based media and high enthusiasm among students, with 84.2% recognizing its importance and 94.2% owning compatible devices. The results highlight the necessity for print-based learning media integrated with AR technology to deliver three-dimensional and realistic visualizations. This approach effectively bridges theoretical concepts and interactive representations, addressing comprehension challenges. The study concludes that AR-integrated learning tools have significant potential to enhance engagement and understanding in biology education, emphasizing the importance of their development and implementation.